Soil Characteristics and Hydromorphological Patterns Control Denitrification at the Floodplain Scale - Kaden, Ute Susanne; Fuchs, Elmar; Geyer, Sophie; Hein, Thomas; Horchler, Peter; Rupp, Holger; Scholz, Mathias; Schulz-Zunkel, Christiane; Weigelhofer, Gabriele (Frontiers in Earth Science, 2021)
Nitrate pollution in aquatic ecosystems is still a major problem in Germany. Although the dynamics of various nitrate-related processes in floodplains remain partially unclear, there is a great potential to permanently remove nitrate from aquatic systems through denitrification as a relevant ecosystem function. However, the controlling factors and the dimension of the denitrification potential are still not fully understood due to the high complexity of the process, various possible explanatory variables, and the high spatial and temporal heterogeneity in floodplains. This study presents the combined assessment of potential soil denitrification rates, physical and chemical soil parameters, and hydrological parameters from six floodplains of four large German rivers, namely the Rhine, the Elbe, the Weser, and the Main. Based on multivariate statistics, results show that the denitrification potential of soil was largely unaffected by hydrology but almost solely controlled by soil pH. We hypothesized that these estimates could be further specified by incorporating the duration of average inundation, as this accounts for water saturation and nutrient supply - the major controlling variables for denitrification. Results provide evidence that the denitrification potential can only be fully exploited in frequently inundated floodplains. Thus, despite favorable soil conditions for denitrification, floodplains that have suffered from anthropogenic impacts lose their importance in nitrate removal for the river system. We conclude that pH and lateral hydrological connectivity are likely to be key factors that should be considered when estimating denitrification as an ecosystem function.